Hubungan Kejadian Gastritis dengan Riwayat Penggunaan Obat Anti Inflamasi Non Steroid (OAINS) pada Pasien yang Melakukan Pemeriksaan Endoskopi - Nirmala Putri, Kintan Nandini; Apriliany, Fitri; Ramdhany, Muh. Wisda Praja (Biocity Journal of Pharmacy Bioscience and Clinical Community, 2024)
Gastritis is inflammation of the gastric mucosa, one of which is caused by the use of non-steroidal anti-inflammatory drugs (NSAIDs). It is very common that NSAIDs are used to treat pain, fever, and inflammatory processes. This study aims to examine the relationship between the incidence of gastritis and a history of NSAIDs use. The research method use in this study is a retrospective cohort design of which the data is collected through interview of patients and their families. The patients medical records at the Mataram City Regional Hospital was also collected. Testing was carried out using the Pearson Correlation test. The result shows that gastritis patients were dominated by people aged 36-55 years (46.43%) and 49 of them were female (58.33%). The Pearson Correlation test shows no significant relationship between the incidence of gastritis and a history of NSAID use, with a p-value> 0.05 and an r-value < 1. This indicates a weak relationship between gastritis and the use of NSAIDs. Therefore, the history of NSAIDs use is insignificant as the main reason for gastritis. Gastritis can also be caused by other factors such as age, lifestyle, and stress levels.